Participating with Feminist Pedagogies and the Narrative Biographical Method in Teacher Training - Martínez Martín, Irene; Bejarano Franco, María Teresa; Téllez Delgado, Virtudes (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In the context of the pandemic, new formulas for executing gender-based violence have appeared. This violence affects participatory processes in educational centers. The objective of this article is to show how feminist pedagogies respond to this situation from the biographical-narrative method. The main conclusions provide the existing benefits of the dialogue between feminist pedagogies and the biographical-narrative method as a basis for intervening in situations of inequality generated by the violence that has occurred and being able to lay the foundations for democratic participation in formal educational spaces.